Frequency and port reconfigurable MIMO antenna for UWB/5G/WLAN band IoT applications. Issue 7 (8th April 2021) - Mathur, Rohit; Dwari, Santanu
Abstract: In this communication, a new compact multiple‐input‐multiple‐output (MIMO) antenna design with frequency and port reconfigurable feature has been presented. The design consists of four orthogonally placed annular ring‐shaped UWB monopole elements. Wideband to narrowband switching of each monopole element is done by PIN diodes placed between the fed line and stepped‐impedance resonating stubs (SIRS). The reconfigurable frequency states are: UWB, mid‐band 5G and WLAN. In narrowband, frequency spectrum is tunable using varactor diodes placed at middle of SIRS. The antenna ports can be tuned to operate as 4‐port, or 2‐port MIMO and it is also possible that all the ports operate at different frequency simultaneously. The concept is proved by simulation and measurement results which includes S‐parameters, radiation patterns, gains, and envelop correlation coefficients.